2016
DOI: 10.1158/1535-7163.mct-15-0521
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of UAB30 in Pediatric Renal and Hepatic Malignancies

Abstract: Rare tumors of solid organs remain some of the most difficult pediatric cancers to cure. These difficult tumors include rare pediatric renal malignancies such as malignant rhabdoid kidney tumors (MRKT) and non-osseous renal Ewing sarcoma, and hepatoblastoma, a pediatric liver tumor that arises from immature liver cells. There are data in adult renal and hepatic malignancies demonstrating the efficacy of retinoid therapy. The investigation of retinoic acid therapy in cancer is not a new strategy, but the widesp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We have previously demonstrated that UAB30 causes decreased cell migration and invasion in other pediatric solid tumors [19, 20], prompting us to investigate whether similar phenotypic changes occur in MB PDX cells following RA or UAB30 treatment. Using Transwell™ plates, we noted that both RA and UAB30 significantly decreased cell migration and invasion in all three MB PDXs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that UAB30 causes decreased cell migration and invasion in other pediatric solid tumors [19, 20], prompting us to investigate whether similar phenotypic changes occur in MB PDX cells following RA or UAB30 treatment. Using Transwell™ plates, we noted that both RA and UAB30 significantly decreased cell migration and invasion in all three MB PDXs.…”
Section: Resultsmentioning
confidence: 99%
“…Following injection of D425 cells (2.5 × 10 6 ) into the right flank of athymic nude mice, animals were randomized to receive vehicle-treated, RA-treated (53 mg/kg/day), or UAB30-treated chow (100 mg/kg/day) (n = 10 mice per group). These doses were based on previous animal studies and have been shown to be well-tolerated in this species [19, 20]. Flank tumors were measured twice per week and animals were euthanized when tumors reached IACUC parameters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations